ULASAN KONSEP: PENDEKATAN PSIKOLOGI INDIJINUS - Hakim, Lukman Nul (Jurnal Aspirasi, 2014)
Psychological scientists from non western countries questioning the validity and relevance of psychological theories built by European-American psychologist used to study the condition of non-western societies. Psychology Theories from the west were built from western culture with respondents from medium socio economic groups and mostly students, and it is considered incompatible with the conditions of nonwestern societies. Therefore, there is a growing need for the contextually and culturally campatible pscyhology theory and it manifests in the indigenous psychology movement, led by psychology scientists from non-western countries. This article explained what is meant within digenous psychology, its difference with cross-cultural psychology, and things need to be strengthened by indigenous psychology movement, so that it can stand in line with established paradigms of psychology.